Isolated Liver Metastasis of Sacrococcygeal Chordoma: Case Report and Review of the Literature - Murat Akyol; Umut Varol; Ibrahim Yildiz; Ibrahim Vedat Bayoglu; Yasar Yildiz; Lutfiye Demir; Ahmet Dirican; Alper Can; Suna Cokmert; Mine Tunakan Oztop; Ahmet Alacacioglu; Yuksel Kucukzeybek; et al. (Case Reports in Oncological Medicine)
Chordomas are rare neoplasms arising from notochordal remnants and may develop anywhere in the body while the most common anatomic site is the sacrococcygeal area. The most effective treatment of chordoma is surgery. Chordomas rarely metastasize to lung, bone, soft tissue, liver, lymph nodes, and skin. However, there is currently no standard systemic treatment for advanced stage chordoma. Here, we reported a rare presentation of chordoma patient with liver only metastases and poor prognosis.